Correlation Modeling Algorithm of CEO Cultural Heterogeneity Monitoring and R&D Expenditure on Enterprise Asset Value based on EEG Data Acquisition Equipment - Tang, Chia-Hsien; Wei, Li; Lee, Yen-Hsien (International Conference on Inventive Computation Technologies (Online), 2022)
This paper develops an EEG acquisition system based on electroencephalogram (EEG) electrodes and a portable wireless terminal. A flexible polyester fiber (fabric) substrate graphene fabric electrode was prepared by vacuum filtration. The functional background heterogeneity of the board of directors was positively correlated with R&D expenditure, the board education level heterogeneity was negatively correlated with R&D expenditure, and the board industry background heterogeneity Sex has no significant effect on R&D spending. The current asset ratio and the guaranteed asset ratio are significantly positively related to its stock price; the net asset per share is significantly positively related to the company's stock price; earnings per share and capital structure have no value correlation.